Thrombocytopenia after Hematopoietic Stem Cell Transplantation in Pediatrics and Adults: A Narrative Review Including Etiology, Management, Monitoring, and Novel Therapies - Kalantari, Amirali; Karimizadeh, Zahra; Jafari, Leila; Behfar, Maryam; Hamidieh, Amir Ali (Seminars in Thrombosis and Hemostasis, 2025)
Thrombocytopenia following hematopoietic stem cell transplantation (HSCT) is a common complication that is associated with a remarkable increase in morbidity and mortality. Post-HSCT thrombocytopenia is a multifactorial condition with several mechanisms, including reduced platelet production in bone marrow, immune-mediated platelet destruction, and consumptive thrombocytopenia. Graft-versus-host disease (GVHD), medications, infections, and autoimmune mechanisms are potential risk factors for post-HSCT thrombocytopenia. Management of post-HSCT thrombocytopenia primarily focuses on supportive care through platelet transfusions. Moreover, immunosuppressive agents are used to target immune-mediated mechanisms. Thrombopoietin receptor agonists and complement inhibitors are novel treatment options with promising results and fewer side effects. However, further research is essential to establish treatment protocols and improve patient care. In this review, we provide a better understanding of the pathophysiology and risk factors associated with post-HSCT thrombocytopenia for early detection and intervention, ultimately aiming to reduce complications.
Keywords: hematopoietic stem cell transplantation; thrombocytopenia; thrombopoietin receptor agonists